Ecotoxicological monitoring of urban reservoir sediment located in the coastal region of northeastern Brazil - Nobrega, Thiago Farias; Souza, Raquel Franco; Medeiros, Guilherme Fulgencio (Ciência e Natura, 2020)
The Extremoz lake, Northeastern Brazil, is an urban water reservoir, used for domestic and industrial activities. The objective of this work was to analyze the quality of the bottom sediment of three sampling stations (T1, T2 and T3) with heterogenous human occupation level. The samples of sediment from these stations was collected monthly (February to November 2014). This analysis involved the concentration of metals (Cd, Cu, Cr, Pb, Ni, F e and Zn), content of organic matter (OM), carbonate (CaCO3), granulometry and acute toxicity of sediment in ten days bioassays with the amphipod Hyalella azteca, as well as monthly rainfall data and the occupation of the surroundings of the water body. The number of toxic events to H. azteca is higher in the rainy months (March, May, June, July and September) and in the more urbanized station (T2). Some variable exhibit positive correlation, as the heavy metals, OM and the silt-clay grain sizes. This is expected because the OM and the fine fractions of the sediment have a higher specific surface area and hence more binding sites for the heavy metals.